Rehabilitating Transcendental Arguments: A Dialectical Dilemma for Stroud’s Meta-Epistemological Skepticism - Simon Schüz (Ergo, An Open Access Journal of Philosophy)
The aim of this paper is to shake up the consensus view on transcendental arguments (TAs) that the ambitious “world-directed” kind fails and that only moderate, “belief-directed” transcendental arguments have a claim to validity. This consensus is based on Barry Stroud’s famous substitution objection: For any transcendental claim ‘p is an enabling condition for X’ we can readily substitute ‘the belief that p’ for ‘p’. I depart from the observation that the force of Stroud’s objection depends on it being applicable to any world-directed TA whatsoever. This requires a much more substantive justification than is commonly supposed. I rehabilitate world-directed TAs by posing a dialectical dilemma for the Stroudian skeptic: a certain moderate TA is required to uphold the skeptical challenge, but this TA brings with it the commitment to a distinction which restricts the scope of the challenge, namely to ‘empirical’ instead of ‘transcendental’ beliefs about the world. The positive result is a new way of understanding what world-directed transcendental arguments are: a way of showing us which of our beliefs about the world are true because they are, in the sense of Wittgenstein’s meter-measure analogy, constitutive of our very standard for objectivity.